Minding rights: mapping ethical and legal foundations of ‘neurorights’ - Ligthart, S; Ienca, M; Meynen, G; Molnar-Gabor, F; Andorno, R; Bublitz, C; Catley, P; Claydon, L; Douglas, T; Farahany, N; Fins, JJ; Goering, S; et al. (Cambridge University Press, 2023)
The rise of neurotechnologies, especially in combination with artificial intelligence (AI)-based methods for brain data analytics, has given rise to concerns around the protection of mental privacy, mental integrity and cognitive liberty – often framed as “neurorights” in ethical, legal, and policy discussions. Several states are now looking at including neurorights into their constitutional legal frameworks, and international institutions and organizations, such as UNESCO and the Council of Europe, are taking an active interest in developing international policy and governance guidelines on this issue. However, in many discussions of neurorights the philosophical assumptions, ethical frames of reference and legal interpretation are either not made explicit or conflict with each other. The aim of this multidisciplinary work is to provide conceptual, ethical, and legal foundations that allow for facilitating a common minimalist conceptual understanding of mental privacy, mental integrity, and cognitive liberty to facilitate scholarly, legal, and policy discussions.